1981
DOI: 10.1001/archderm.117.12.770
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermia in the treatment of psoriasis

Abstract: The effectiveness of commercially available, chemically generated, topical exothermic pads that elevate skin surface temperature from 42 to 43 degrees C was stressed in 22 patients with psoriasis. Control sites were treated with conventional modalities such as Goeckerman's regimen, as well as with occlusion with nonexothermic pads. Skin lesions in 19 patients disappeared after the use of hyperthermia. The average time required for complete regression in the treated areas was 27 days with hyperthermia, compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…Orenberg's study in 1980, which used ultrasound induced heat to treat psoriasis, showed a benefit for psoriasis lesion remission [29]. Later it was demonstrated that hyperthermia induced by topical exothermic pads [30], infrared [31], or microwave [32] was also effective for psoriasis plaques. The advantage of using a hot water bath is that it is a simple, inexpensive approach that can be used to treat relatively large body areas [33].…”
Section: Discussionmentioning
confidence: 99%
“…Orenberg's study in 1980, which used ultrasound induced heat to treat psoriasis, showed a benefit for psoriasis lesion remission [29]. Later it was demonstrated that hyperthermia induced by topical exothermic pads [30], infrared [31], or microwave [32] was also effective for psoriasis plaques. The advantage of using a hot water bath is that it is a simple, inexpensive approach that can be used to treat relatively large body areas [33].…”
Section: Discussionmentioning
confidence: 99%
“…With the variety of treatments available today, it is possible to improve the quality of life of nearly all psoriatic patients. [50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66] According to a recent economic study on the cost of psoriasis treatments, overall expenses increase with the severity of the disease. 67 Taking into consideration that Dead-Sea climatotherapy is similar in cost regardless of the severity of the disease, climatotherapy gets an extra score for treatment of severe patients.…”
Section: Discussionmentioning
confidence: 99%
“…Local hyperthermia has been found to be effective in the treatment of psoriasis (14,17). Psoriatic scales showed reduction in neutrophil chemotactic activity after local hyperthermia (9).…”
Section: Discussionmentioning
confidence: 99%
“…Studies demonstrating abnormalities of the humoral immune system in psoriasis patients have also been reported (6,7,11); however, chemotaxis studies of the humoral system are controversial (10,14). Recently, local hyperthermia has been found to be effective in the treatment of psoriasis (14,17). The action mechanism of this therapy is still unknown.…”
Section: Introductionmentioning
confidence: 99%